We are friends: A case study of children’s tolerance experience in komunitas anak Sabtu Ceria to counter religious radicalism - Tuasuun, Magyolin Carolina; Tuasuun, Dina Novita (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Living in a multicultural society requires openness and acceptance of different people. Nevertheless, it takes work for radicals to open up, accept, and appreciate differences. Religious radicalism is a challenge that we still face today. Radicalism harms life, as occurred in several countries worldwide. Therefore, the spread of religious radicalism must be stopped, particularly for children as the future of the world. This article offers the concept of heterogeneous friendship as a powerful tool for children to open up and appreciate differences. Heterogeneous friendship becomes a hidden curriculum for children. By using a case study, it shows that through friendship with children from different backgrounds, children can share experiences and get to know each other more deeply. Thus, this experience in heterogeneous friendships is a robust learning process to foster and develop tolerance amid multicultural life.